THERMODYNAMIC ANALYSIS AND PREDICTION OF HIGH-TEMPERATURE OXIDATION OF COMPOSITE ALLOYS - Kindrachuk, Myroslav; Kharchenko, Volodymyr; Kornienko, Anatoliy; Humeniuk, Ihor; Hlovyn, Mykhailo (Problems of Friction and Wear, 2024)
The thermodynamic analysis of the interaction of composite powder alloys of the Co-TiC system with air is carried out. The main regularities of their oxidation are established. The mutual influence of the content of chromium and titanium carbide on the quantitative composition of oxidation products is shown.Based on the analytical studies, the dependence of the quantitative and qualitative composition of the products of interaction with air of powdered alloys of the Co-TiC system on the ratio of their components was determined. The formation of protective layers can be predicted, and their formation can be controlled by selecting appropriate alloying elements and strengthening phases by thermodynamic analysis.The general laws of oxidation of powdered composite alloys of the Co-TiC system have been established. The influence of chromium content in the material on the composition and properties of oxide layers is shown. It was found that at a high chromium content in the matrix (more than 25% by volume), the brittleness of the oxide layer increases, which will lead to its intensive wear.